The impact of blockchain on data integrity and security in distributed systems - Annapureddy, Govardhan Reddy (Eastasouth Institute, 2024)
Blockchain has toured the technological world as a revolutionary platform powering safe and secured storing of information across many sectors including digital currency and supply systems. This paper discusses the potential of this technology and the essential role it plays in the management of data integrity and security in distributed systems. It starts with a brief discussion of the key concepts of blockchain namely decentralization, the ledger is not controlled by the parties to the transaction or by any third party, immutability of records on the blockchain, the records on a blockchain cannot be tampered with once they have been put on the blockchain, and transparency, everybody can see the record but cannot influence it. The paper then looks at how these principles improve data security and data integrity as compared to centralized approach. Besides, it also looks at some of the drawbacks and possible limitations of blockchain about data consistency and protection again also giving scenarios that support its efficiency.